Secuencias de 658 pares de bases (fragmento barcode) del gen citocromo c oxidasa subunidad I (COI) de mosquitos de los géneros Aedeomyia, Anopheles, Coquillettidia, Culex, Haemagogus, Mansonia, Nyssorhynchus, Ochlerotatus, Psorophora y Uranotaenia de Argentina. - Laurito, Magdalena (2023)
The family Culicidae is represented by 244 species in Argentina, many of them with epidemiological importance. DNA barcodes are effective tools for identifying mosquito species, for knowing genetic variability, and for establishing phylogenetic relationships. This work aims to explore mosquito diversity employing different species delimitation approaches and to establish formally a DNA barcode library for the Argentinian mosquito fauna. Barcode fragments of 80 specimens of Argentinian mosquitoes of 28 species of the genera Aedeomyia Theobald (Diptera: Culicidae), Anopheles Meigen (Diptera: Culicidae), Coquillettidia Dyar (Diptera: Culicidae), Culex L. (Diptera: Culicidae), Haemagogus Williston (Diptera: Culicidae), Mansonia Blanchard (Diptera: Culicidae), Nyssorhynchus Blanchard (Diptera: Culicidae), Ochlerotatus Lynch-Arribálzaga (Diptera: Culicidae), Psorophora Robinneau-Desvoidy (Diptera: Culicidae) and Uranotaenia Lynch-Arribálzaga (Diptera: Culicidae) were sequenced. Another 82 sequences were obtained from public databases to establish the phylogenetic relationships using Maximum Likelihood and Bayesian Inference, and the species boundaries based on three approaches (ABGD, GMYC, and mPTP). Sixteen of the 28 species sequenced were recovered as monophyletic, of which 12 were also recognized as molecular operational taxonomic units according to the three methodologies. The disparity between morphology and barcode-based identifications could be explained by synonymy, species complexes occurrence, hybridization, incomplete lineage sorting, or the effect of the geographical scale of sampling. Twenty of the 28 sequenced species are new barcodes for Argentina and 11 are the first for science. This increases from 31 to 52 (12.7 to 21.31%) and from six to 10 (28.57 to 47.62%) the number of species and genera, respectively, with barcode sequences in Argentina. New species records are provided.